(untitled) (REMUNOM, 2026)
Objective: To analyze concepts and factors associated with body dissatisfaction in adolescents. Material and Methods: This narrative and integrative literature review synthesizes definitions of body image and evidence on sociocultural determinants and related outcomes, including assessment instruments reported in studies with adolescent populations. Results: Body image is a complex, multidimensional construct comprising perceptual and attitudinal components, and body dissatisfaction is emphasized as part of the attitudinal dimension, expressed as discomfort and negative feelings about one’s appearance. Media, family, and peers contribute to the internalization of socially prescribed beauty ideals, increasing vulnerability during adolescence. Negative body evaluation is associated with disordered eating behaviors and may contribute to outcomes such as eating disorders, depressive symptoms, and social withdrawal. Conclusion: Body dissatisfaction in adolescence is prevalent and multifactorial; broader use of validated assessment protocols and measures for the Brazilian population is needed to support effective preventive strategies and early interventions.